Foundations of neuroeconomic analysis - Glimcher, Paul W. (New York ; Oxford : Oxford University Press, 2011)
Neuroeconomics has emerged at the border of the social and natural sciences. This book argues that a meaningful interdisciplinary synthesis of the study of human and animal choice is not only desirable, but also well underway, and so it is time to develop formally a foundational approach for the field.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Cognitive neuroscience; Neuroeconomics; Decision making; Decision making -- Physiological aspects; Choice (Psychology)